Prostaglandin and prostamide concentrations in amniotic fluid of women with spontaneous labor at term with and without clinical chorioamnionitis. (December 2020) - Peiris, Hassendrini N; Romero, Roberto; Vaswani, Kanchan; Gomez-Lopez, Nardhy; Tarca, Adi L.; Gudicha, Dereje W.; Erez, Offer; Maymon, Eli; Reed, Sarah; Mitchell, Murray D
Highlights: Mass spectrometry elucidated of prostaglandins and prostamides in term pregnancy amniotic fluid. Spontaneous labor at term with is characterized by elevated prostaglandins but not prostamides. Chorioamnionitis had elevated prostaglandins but not prostamides. Abstract: Objective: Prostaglandins (PGs) are considered universal mediators for the process of physiological parturition. This is based on observations that amniotic fluid concentrations of PGs are elevated prior to and during the onset of labor (mostly utilizing immunoassays). Distinguishing PGs from similarly structured molecules (i.e. prostamides; PG-EA) is difficult given the cross-reactivity of available antibodies and the chemical similarity between these compounds. Herein, this limitation was overcome by utilizing mass spectrometry to determine PG and PG-EA concentrations in amniotic fluid of women with spontaneous labor at term and in those with clinical chorioamnionitis (CHAM), the most common infection-related diagnosis made in labor and delivery units worldwide. Study Design: Liquid chromatography-tandem mass spectrometry (LC MS/MS) was used to determine the PG and PG-EA content in amniotic fluid samples of women with spontaneous labor at term with ( n  = 14) or without ( n  = 28) CHAM. Controls included women who delivered at term without labor ( n  = 10). Results: PGE2, PGF2α, and 13, 14-dihydro-15-keto-PGF2α (PGFM) were higher in amniotic fluid of women with spontaneous labor at term than in those without labor. PGE2, PGF2α, and PGFM were also higher in amniotic fluid of women with CHAM than in those without labor. However, PGE2 -EA and PGF2α -EA were lower in amniotic fluid of women with CHAM than in those without CHAM. The ratios of PGE2 to PGE2 -EA and PGF2α to PGF2α -EA were higher in amniotic fluid of women with spontaneous labor at term with or without CHAM than in those without labor; yet, the ratio of PGF2α to PGF2α -EA was greater in women with CHAM than in those without this clinical condition. Conclusions: Spontaneous labor at term with or without CHAM is characterized by elevated amniotic fluid concentrations of prostaglandins (PGE2, PGF2α, and PGFM) but not prostamides. Quantification of these products by LC MS/MSlc==may potentially be of utility in identifying their physiological functions relevant to parturition. Summary: Prostaglandins (PGs) are critical for the onset and progression of labor. Structural similarities of PGs and prostamides (PG-EA) prevents their specific identification by immunoassay. We utilized LC MS/MS to determine PG and PG-EA content in amniotic fluid (AF) of women with spontaneous labor at term with or without CHAM and women who delivered at term without labor. Higher aamniotic ffluid PG levels were observed in women with spontaneous labor with and without CHAM compared to women delivering without labor. PG-EA levels in amniotic fluid of women with spontaneous labor and CHAM were lower than in women with spontaneous labor without CHAM but not those without labor. Ratios of PGs to PG-EAs were higher in AF of women with labor and CHAM compared to those without labor. Delineation of these products by LC MS/MS may potentially be of utility in identifying their physiological functions relevant to parturition